The Effect Of WEDM Cutting Parameter On Inconel 718 Subsurface Microhardness - Kasim, Mohd Shahir; Mohd Zahudi, Mohd Sufri; Che Haron, Che Hassan; A Ghani, Jaharah; Raja Abdullah, Raja Izamshah; Mohd Isa, Mohd Hanafiah; Saedon, Juri; Roni Sahroni, Taufik; Ito, Teruaki (Universiti Teknikal Malaysia Melaka, 2014)
This paper reports on the effect of wire electrical discharge machine (WEDM) cutting parameter on the subsurface hardness of Inconel 718. The response surface methodology (RSM)using Box-Behnken design was used to conduct the experiment and analyze the relationship between control variables and responses. A total of 8 runs was carried out during the experiment. The Historical Data of Response Surface Methodology (RSM) was used as a tool of design of experiment (DOE). The selected WEDM parameters were Voltage (40-42V), feed rate (6-8V) and current (0.5-1.5 mm/min). The subsurface hardness was measured at the distance of 50 μm, 100 μm, 300 μm, 500 μm beneath the cutting surface. Observation of the results shows that the subsurface hardness is higher at the distance of 50μm than 500 um. The hardness was gradually decreased toward bulk hardness of HV0.1 270. Analysis of variance (ANOVA) was used to identify the significant effect of the factors on the response. Based on the analysis, feed rate and current were found to be the most significant factors in hardness change. Mathematical models were developed for hardness prediction with an average error of 2.7%. The minimum hardness change of HV0.1 30 was obtained by the combination of feed rate = 1.29 mm/min, servo voltage = 40.33 V,current = 7.94 A.